The Effect of Marketing Systems, Technology Utilization, and Capital Access on Going Concern in Small and Medium-Sized Enterprises - Ridwan, Ridwan; Parwati, Ni Made Suwitri; Indriasari, Rahayu; Jamaluddin, Jamaluddin; Halwi, Muh. Darma (International Review of Management and Marketing, 2026)
This study explores the contextual factors influencing the principle of going concern in small and medium-sized enterprises (SMEs) in Donggala, Central Sulawesi. The purpose of the study is to analyze how marketing systems, technology utilization, and access to capital affect the sustainability of SMEs in the household goods sector. A quantitative approach was used, with data collected through questionnaires and interviews from 168 SME owners and managers. The data was analyzed using Partial Least Squares (PLS) analysis. The results reveal that while the marketing system does not significantly impact business sustainability, the use of technology, such as grinding machines, positively affects productivity and product quality. Additionally, access to capital plays a crucial role in ensuring business continuity, as effective capital management mitigates financial challenges. On the other hand, access to information and business planning do not show a significant effect on the principle of going concern. Despite the availability of information technology, SME owners in Donggala continue to prioritize traditional methods, limiting the potential benefits of technological advancements. The study emphasizes the need for government intervention to better integrate information technology, thereby supporting the industry’s growth and enabling SMEs to access broader markets.